Synthesis and characterization of nano sized (Zn,Cd)S mixed phosphors - Singh, Ranjeet; Dubey, Vikas; Tiwari, Ratnesh (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Present paper reports synthesis and characterization of (Zn,Cd)S mixed phosphors. Sample was synthesized with modified chemical route method which is suitable for large scale production and economical with pollution free technique. Prepared sample was characterized by PXRD (Powder X-ray Diffraction technique) and average crystalline sizes were calculated by Debye-Scherer formula which was verified by FEGSEM (Field emission gun scanning electron microscopy) technique. The average particles sized were found at 5-55nm range. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->